Healthcare financing in Poland in scope of Medical Rescue - Płaziak, Robert (Journal of Education, Health and Sport, 2019)
This article discusses the financing and organizational structure of the State Emergency Medical Services in Poland (PRM) relating to fundamental documents as stated on February 2019. It presents a historical outline of the formation and organization of this part of the medical domain which are Emergency Medical Services treated as a part of the National Health system. The article sums up with a thesis, that medical activity in scope of financing and organizational structure in Poland can be classified as well-functioning, however without proper correlation with other parts of the services we might expect issues with cooperation. To mitigate this risk, we must stop diversification of medical activities and focus on complexation of services in large medical entities, modifying it accordingly to the principles of the evolution without introducing irrational changes, at the same time modernizing and following science development effects. Only a well-functioning health system with Emergency Medical Services being a part of it, not a separated, efficient company, will result in a significant improvement for those in need.